A Convenient Technique to Fix Suspension Cells on a Coverslip for Microscopy. Issue 1 (1st September 2015) - Mihara, Keiko; Nakayama, Tomofumi; Saitoh, Hisato
Abstract: Human myeloid HL‐60 cells are usually cultured in suspension in medium containing 5% to 10% fetal bovine serum (FBS) and thus are often difficult to adhere to a coverslip. In this unit, we describe how removal of FBS from the culture medium facilitates adhesion of HL‐60 cells to coverslips. Importantly, HL‐60 cells that adhere to the coverslips immersed in FBS‐free medium can be immobilized in situ by conventional chemical fixatives and thus permeabilized for probing cellular structures using specific dyes and/or reagents, followed by microscopic observation. All‐ trans ‐retinoic‐acid‐exposed differentiated HL‐60 cells, which have properties similar to neutrophils, can also adhere efficiently to coverslips in FBS‐free medium. Because the procedure is not complex and special equipment is not required, the simplicity and cost effectiveness of this FBS‐free cell adhesion protocol may be beneficial to researchers who are interested in assessing the structure and function of suspension cells using microscopy. © 2015 by John Wiley & Sons, Inc.